Plasma corticosterone concentration in laying hens (Gallus Domesticus) during the laying period - Aleš Pavlík; Zdeněk Havlíček (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2004)
The aim of this work was to study corticosterone concentration in the plasma of laying hens (gallus domesticus) during the laying period. The experiment included 12 ISA Brown laying hens, which were caged in enriched cage system according to EU directive 1999/74. They were fed by complete diet for laying hens. Blood samples were taken between 15th and 75th week of age. Mean corticosterone concentration during the whole period was 2.86 ± 0.086 nmol.l-1 and ranged from 1.76 ± 0.135 to 3.98 ± 0.0357 nmol.l-1. Plasma corticosterone concentration increased significantly (P≤0.01) at the beginning of the laying period. Then followed slight variation until 47th week of age. Corticosterone concentration increased significantly (P≤0.01) again at 52nd week of age to 3.98 ± 0.236 nmol.l-1. From 58th week of age to end of laying period plasma corticosterone concentration decreased and reached the value of 2.22 ± 0.210 nmol.l-1.